Nursing Thesis Database Project: a cooperative venture for nursing faculty and computer science professionals. - Schermer J; Geisler E; Vang P (Computers in Nursing)
The authors describe the development of an educational database project designed to promote the accessibility of nursing administration theses data for graduate students and faculty in a university nursing administration program. The roles of a nursing faculty member, a computer laboratory administrator, and a programmer are detailed as they work together from the concept phase of the project through its evaluation. The results of their combined efforts provided a reliable and efficient database, resulted in a closer interdisciplinary relationship, and allowed valuable nursing research information to be shared more widely within the university.